Heuristics and operational research in emergency situations and civil defence education - Bereš, Paun J.; Bereš, Kristian P. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper presents  problem solving using heuristics and operational research in order to make appropriate decisions in emergency situations with a particular emphasis on the application of a heuristic model of team training for emergency situations. It is intended for military command and teaching personnel as well as for civil defense personnel (Department of Emergency Management) and local government authorities (administrative district chiefs and mayors - commanders). The heuristic approach to problem solving should enable adequate decision making for command staff from the local to the national level after the proclamation of emergency and a state of emergency in some regions or the whole territory of Serbia.
Keywords: civil protection; problem-solvin; operator; operations research; heuristics; defense; decision